Community Empowerment Based on Local Products (A Study of Lontong Village in Banyu Urip Lor, Kupang Krajan Subdistrict, Sawahan District, Surabaya City - Delima Simbolon; Sasmito Jati Utama (Jurnal Administrasi Publik, 2026)
This study analyzes community empowerment in Lontong Village, Banyu Urip Lor, Surabaya City, which has developed as a thematic village based on home-based lontong production. Despite having significant local economic potential, community business development still faces various challenges, such as limited formal training, weak business management, rising production costs, and insufficient protection for local businesses. Previous research has primarily focused on the economic and marketing aspects of MSMEs, while studies on the community empowerment process and collaboration among stakeholders in supporting the sustainability of thematic villages remain limited. The method used is descriptive qualitative research employing interview, observation, and documentation techniques. The analysis was conducted based on Suharto’s (2005) community empowerment theory, which encompasses enabling, strengthening, protection, support, and maintenance. The research results indicate that community empowerment in Kampung Lontong has progressed fairly well regarding the indicators of enabling, protection, and maintenance, but remains suboptimal regarding the indicators of strengthening and support, particularly in terms of formal training, business record-keeping, halal certification, and ongoing mentoring. These findings underscore that local product-based empowerment requires collaborative support from the government, universities, and the community to develop a more effective, inclusive, and sustainable MSME empowerment model.